2019
DOI: 10.1101/565770
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time-series genome-centric analysis unveils bacterial response to operational disturbance in activated sludge

Abstract: Understanding ecosystem response to disturbances and identifying the most critical traits for the maintenance of ecosystem functioning are important goals for microbial community ecology. In this study, we used 16S rRNA amplicon sequencing and metagenomics to investigate the assembly of bacterial populations in a full-scale municipal activated sludge wastewater treatment plant over a period of three years, including a period of nine month of disturbance, characterized by short-term plant shutdowns. Following t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…The Gordonia metagenome-assembled genome (MAG) was one of the 173 MAGs obtained in a previous study using data from a time-series analysis of a municipal full-scale activated sludge plant [30]. The refined Gordonia sp.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Gordonia metagenome-assembled genome (MAG) was one of the 173 MAGs obtained in a previous study using data from a time-series analysis of a municipal full-scale activated sludge plant [30]. The refined Gordonia sp.…”
Section: Resultsmentioning
confidence: 99%
“…Reads were recovered from the Gordonia MAG assembled in Perez 2019 [30]. We confirmed that all scaffolds belonged to the same MAG by calculating the abundance and tetranucleotide frequency correlation of each scaffold in the MAG.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations